Simulation of Convective Heat Transfer in 3D Forward Facing Step Using Various Turbulence Models - Raj Sarath; Janardanan Sarasamma Jayakumar (Journal of Engineering and Technological Sciences, 2020)
In this work, a modified solver from the OpenFOAM 4.1 software was used to study the fluid flow and heat transfer characteristics over a forward facing step (FFS) considering various turbulence models, viz., k-Îµ, k-Ï‰, k-Ï‰ SST and v2-f. Numerical computations were performed using a newly developed transient solver, pisoTempFoam. Modeling and meshing of the geometry and setting of the boundary conditions were done with OpenFOAM. The bottom (upstream, step and downstream) walls were heated at a constant temperature of 350K, while the fluid inlet temperature was 298K. The simulation results were compared with those available in the literature. Variation of skin friction coefficient (Cf), coefficient of pressure (Cp), and Nusselt number (Nu) for different Reynolds numbers (Re), contraction ratios (CR) and different fluids are presented. This article also presents information about recirculation bubbles in the upstream and downstream regions of the FFS. The results show that the combined effect of turbulence models and parameters, such as CR, Re and Pr, change the flow and heat transfer characteristics of the FFS. The present CFD simulation plays a pivotal role in the analysis of flow over airfoils at a large angle of attack in heat exchangers and pipes whose area suddenly changes.